Pendidikan Kebangsaan dalam Perspektif Al - Qur'an - Azzah Nor Laila (UPT Pusat Studi Aswaja UNISNU Jepara, 2021)
AbstractProblems of disunity and less of public awareness about the sense of belonging in the nation, often become a trigger for tension and disharmony in social relations. Both within the scope of fellow religious people, as well as within a nation. To mediate this, the planting of a sense of belonging to the nation or education about nationality to the community is important as a solution. This paper aims to find the message of national education in the Qur'an. Al-Qur'an as a Muslim holy book is full of educational values. This paper uses thematic methods and content analysis of the text of the Qur'anic verses about the nation. The findings of national education in the perspective of the Qur'an are recommendations to uphold the equal rights of citizens in a nation. The importance of government cooperation with its people. The peace and tranquility of a country is essentially based on the attitude of its inhabitants, it is carried out by means of gratitude, use of voting rights, deliberation, courtesy and honesty. The importance of introspection and evaluation. Every citizen of the country, both the people and the authorities, must have a mistake. All residents should be aware and admit their mistakes, then correct and apologize to those who are judged and to the Forgiving.Keywords: education, nationality, Qur’an versesAbstrakProblem perpecahan serta kurangnya kesadaran masyarakat tentang sense of belonging pada bangsa, sering menjadi pemicu ketegangan serta disharmoni hubungan sosial. Baik dalam lingkup sesama umat beragama, maupun dalam suatu bangsa. Untuk menengahi hal itu, penanaman sense of belonging pada bangsa atau pendidikan tentang kebangsaan pada masyarakat menjadi hal penting sebagai solusi. Tulisan ini bertujuan menemukan pesan pendidikan kebangsaan dalam al-Qur’an. Al-Qur’an sebagai kitab suci umat Islam sarat dengan nilai-nilai pendidikan. Tulisan ini menggunakan metode tematik serta content analysis terhadap teks ayat-ayat al-Qur’an tentang bangsa. Hasil temuan pendidikan kebangsaan dalam perspektif al-Qur’an adalah anjuran menjunjung kesamaan hak warga dalam suatu bangsa. Pentingnya kerjasama pemerintah dengan rakyatnya. Kedamaian dan ketentraman suatu negara hakikatnya didasarkan pada sikap penduduknya, diantarnya dengan cara bersyukur, menggunakan hak suara, bermusyawarah, santun berpendapat dan jujur. Pentingnya introspeksi dan evaluasi. Setiap penduduk negara baik rakyat maupun penguasa pasti memiliki kesalahan. Hendaknya semua penduduk menyadari dan mengakui kesalahannya, kemudian memperbaiki dan memohon maaf kepada pihak yang didhalimi serta kepada Maha Pengampun.Keywords: pendidikan, kebangsaan, ayat al-Qur’an